(untitled) (New York, 2003)
Nanotechnology, science, and engineering spearhead the 21st century revolution that is leading to fundamental breakthroughs in the way materials, devices, and systems are understood, designed, made, and used. With contributions from a host of world-class experts and pioneers in the field, this handbook sets forth the fundamentals of nanoelectromechanical systems (NEMS), studies their fabrication, and explores some of their most promising applications. It provides comprehensive information and references for nanoscale structures, devices, and systems, molecular technology and nanoelectromechanical theory, and promises to become a standard reference for the field.
Keywords: Molecular electronics,Nanotechnology